Exploring the role of viewers' tweets in French TV political programs: Social TV as a new agora?. (October 2017) - Atifi, Hassan; Marcoccia, Michel
Highlights: Definition of the media background of social TV: hybrid media device, between TV forum and online discussion. Analysis of the pragmatic functions of the tweets displayed in a French "political social TV" program. Questions about the participatory and dialogical dimensions of social TV. Social TV favors participation, but not interaction. Abstract: This paper focuses on 'political social TV'. Social TV corresponds to two phenomena: TV viewers have the opportunity to react to a program by posting tweets, SMS or Facebook messages, and these digital messages are integrated into the TV program. Thus, social TV is intended to allow users to contribute to public discussions and to facilitate the constitution of a transmedia and digital agora. This paper proposes an analysis of the tweets produced by TV viewers, selected by the program director and displayed on screen during the French political TV program Des Paroles et Des Actes, broadcast by France 2 on 6 February 2014. Through the interactional and pragmatic analysis of these messages, several questions will be addressed: what are the addressee and the reception format of these tweets? Who are the authors of these messages? What are the main functions of these tweets? From a more general perspective, this analysis raises questions about the participatory and dialogical dimensions of social TV and the digital agora.